Efeito da suplementação com disseleneto de difenila no metabolismo, imunidade e status oxidativo de vacas leiteiras e seus bezerros - Rodrigues, Cláudia Medeiros (2024)
The aim of this study was to evaluate the supplementation effect with diphenyl diselenide (PhSe)2 carried out during transition period, on metabolism, immunity and oxidative status of female Holstein cows and their calves. Twenty-seven multiparous Holstein females in the transition period were used (n = 27), distributed into three groups (n = 9/ treatment). As well as 18 calves (n = 18), offspring of cows participating in the study, which belong to the groups corresponding to the treatments received by the mothers (n = 6/treatment). The diphenyl diselenide group (DDG) received 3 μmol/kg of (PhSe)2, diluted in 4 mL of dimethylsulfoxide (DMSO), administered by subcutaneous route (SC). The dimethylsulfoxide (DMSOG) and NaCl (NACLG) groups received 4 mL of DMSO and 0.9% NaCl, by the same route. At 42, 28 and 14 days prepartum, and on the calvin day (0) the females were weighed and evaluated for their body condition score (BCS), followed by the administrations. On days 0 (calvin day), 7, 14, 21 and 35 postpartum, BCS assessments were performed, and blood samples were collected. From the first postpartum milking (day 0) colostrum was obtained. Production was measured using an automatic weighing system, and milk samples were collected on days 7, 14, 21 and 35 postpartum. The calves were accompanied from birth to the 70th day of life, in this period they were weighed, the height at the withers was measured and the body condition score evaluated, 24 hours after birth (day 0), and at 14, 28, 42, 56 and 70 days of life, on the same days blood samples were collected. Mothers blood samples were used to determine the variables: plasma fibrinogen, beta-hydroxybutyrate (BHB), calcium (Ca), fructosamine (FRUT), total protein (TP), albumin (ALB), immunoglobulin G (IgG), thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH). In colostrum, brix index and IgG concentrations were evaluated. Milk samples were used for somatic cell (SCC) and total bacterial counts (TBC). Blood samples from calves were used to measure TP ALB, gamma-glutamyl transferase (GGT), IgG, TBARS and GSH. DDG cows had higher values of TP and globulins (GLOB) than DMSOG on day 7, in addition, DDG IgG concentrations were higher than the other groups on days 21 and 35 postpartum. While calves born to females submitted with (PhSe)2 supplementation showed the highest TP, ALB and GLOB averages on day 0, and IgG higher than the other groups on days 0, 14, 56 and 70 of life. Through the results we concluded that the supplementation with (PhSe)2, carried out during the transition period, stimulated postpartum humoral immunity in cows, as well as in calves, offspring of cows submitted to supplementation.